Pemanfaatan Bahan Aditif untuk Menaikkan Nilai Kalor Briket dari Sampah Kota Lhokseumawe - Kartini, Kartini; Irwan, Irwan; Saifuddin, Saifuddin (Jurnal Teknologi, 2024)
This research is the manufacture of briquettes from organic waste which added additives in the form of coconut shell charcoal and wood charcoal using oil and kaolin adhesives. The purpose of the study was to see the quality of briquettes based on constituent materials with a comparison of organic waste and additives. Add additives in the form of coconut shell charcoal and wood charcoal which are varied by 10%, 15%, 20%, 25% and 30% to organic waste then made briquettes. Organic waste mixed with additives has previously been euyeumized for about 12 days and dried until the moisture content of organic waste is a maximum of 10%. Briquette analysis carried out is analyzing water content, ash content, volatile levels, carbon content, and calorific value. From the results of the study, the following data were obtained, the amount of additives added greatly affects the quality of the briquettes produced, In the addition of 20% coconut shell charcoal additives, the results were obtained namely 1% moisture content, 13.60% ash content, 13.68% volatile content and 5,641 cal/g calorific value, The addition of 15% wood charcoal additives obtained results that were 3% moisture content, 13.28% ash content, 8.07% volatile content and 5,809 cal/g calorific value. Overall a good briquette is obtained at the ratio of adding wood charcoal additives + coconut shell charcoal 25%, which is 1% moisture content, ash content 9.37%, volatile content 13.68% and calorific value 6010 cal/g. All test results have met the Indonesian National Standard (SNI).